Dynamic analysis and fault diagnosis of a water hydraulic motor - Chen, Hanxin (2008)
This research is concerned with condition monitoring and fault diagnosis of the piston of the water hydraulic motor by vibration signal analysis. Vibration signatures are obtained from the casing of the water hydraulic motor. The size and locations of straight-line cracks on the piston were introduced for the experiments. The lengths of the short piston cracks and long piston cracks are 5mm and 10mm, respectively. They are in the front and back sections of the piston, respectively. There are four kinds of piston cracks, i.e. back long crack (BLC), back short crack (BSC), front long crack (FLC) and front short crack (FSC).